Exploring Pedagogical and Digital Practices in Vocational Education and Training: Comparing Teacher and Student Perspectives - Ingrid Noguera; Daniel Barrientos; Mónica Torres-Sánchez; Pilar Pineda-Herrero (MDPI AG, 2024)
This article investigates the pedagogical and digital practices of vocational education and training teachers, offering comparative insights from both teacher and student perspectives. To this end, two questionnaires were constructed for teachers and students and then validated by means of inter-judge procedures and expert review. The questionnaires were administered to representative samples of 158 teachers and 309 students in intermediate and higher vocational education and training programs in the Spanish region of Catalonia. Thanks to institutional collaboration, it was possible to obtain both samples by a non-probability sampling technique. The results obtained from the quantitative analyses performed show that while most vocational education and training teachers utilize a combination of active and lecture-based methods, less than a third incorporate online tools, prioritizing institutional platforms. Although both teachers and students acknowledge a diversity of teaching strategies, the latter, particularly female students and those in advanced years or on dual programs, tend to be more critical of the effectiveness of the teaching strategies employed compared to their teachers. The findings underscore the need for vocational education and training programs to enhance digital tool integration and address the varying perceptions of teaching effectiveness to better meet students' expectations and needs.